2018
DOI: 10.3390/agronomy8080140
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Amaranthus hybridus with Multiple Resistance to 2,4-D, Dicamba, and Glyphosate

Abstract: In many countries, Amaranthus hybridus is a widespread weed in agricultural systems. The high prolificacy and invasive capacity as well as the resistance of some biotypes to herbicides are among the complications of handling this weed. This paper reports on the first A. hybridus biotypes with resistance to auxinic herbicides and multiple resistance to auxinic herbicides and the EPSPs inhibitor, glyphosate. Several dose response assays were carried out to determine and compare sensitivity of six population of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Resistance to 2,4-D was confirmed in all the R populations studied for the six dicotyledonous weed species, both thanks to ethylene production and dose-response experiments (Figure 1 and Table 2). The RF (always ≥4) were in the range reported in previous research for A. hybridus [24], P. rhoeas [13,18,27], P. hysterophorus [25] or close relative species to H. incana such as R. raphanistrum [21]. Also, in this work, ethylene biosynthesis supported susceptibility and resistance of all populations; all R plants tested accumulated less ethylene than S plants for each species, as in previous studies [13,28].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Resistance to 2,4-D was confirmed in all the R populations studied for the six dicotyledonous weed species, both thanks to ethylene production and dose-response experiments (Figure 1 and Table 2). The RF (always ≥4) were in the range reported in previous research for A. hybridus [24], P. rhoeas [13,18,27], P. hysterophorus [25] or close relative species to H. incana such as R. raphanistrum [21]. Also, in this work, ethylene biosynthesis supported susceptibility and resistance of all populations; all R plants tested accumulated less ethylene than S plants for each species, as in previous studies [13,28].…”
Section: Discussionsupporting
confidence: 88%
“…It is expected that the number of cases will increase trough the next years due to both new uses of 2,4-D enabled by the introduction of 2,4-D R crops, and also its incremental use due to greater dependence on SAH in response to the emergence of resistance to other herbicides [23]. Among many countries, very important new weeds R to 2,4-D have been cited: Amaranthus hybridus from Argentina [24] and Parthenium hysterophorus from Cuba [25], in which enhanced metabolism seems to be involved, and Papaver rhoeas is now spreading in France and Italy [26]. Other cases have been reported but not yet investigated, including Conyza canadensis from Hungary and C. sumatrensis from France, both found in vineyards, and Hirschfeldia incana from Argentina in winter cereals, reported by the co-author Dr. Vigna [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of glyphosate resistance, it is a triple mutation that confers high levels of resistance and that had not previously been observed in any other species [10,54]. In addition, in Argentina there are also populations of the species with multiple resistance to 2,4-D and dicamba [55]. Therefore, if it is confirmed that the resistant populations of A. hybridus found in Brazil were introduced from Argentina, the scenario faced by Brazilian farmers in the coming years in relation to weed management will be very difficult.…”
Section: History Of Reports Of Herbicide-resistant Weeds In Brazil Pementioning
confidence: 99%
“…Amaranthus species are prone to evolve resistance after repeated exposure to herbicides having the same site of action (SoA). To date, monoecious Amaranthus species have evolved multiple resistance to two different SoAs, A. hybridus to ALS and PSII inhibitors (HRAC group C1), to ALS and EPSPS inhibitors, and recently to EPSPS inhibitors and synthetic auxins . A. retroflexus evolved multiple resistance to two classes of PSII (HRAC group C1 and C2), to ALS and PSII inhibitors, whereas another biotype proved to be resistant to ALS and PPO inhibitors .…”
Section: Introductionmentioning
confidence: 99%
“…To date, monoecious Amaranthus species have evolved multiple resistance to two different SoAs, 6 A. hybridus to ALS and PSII inhibitors (HRAC group C1), 7 to ALS and EPSPS inhibitors, 8 and recently to EPSPS inhibitors and synthetic auxins. 9 A. retroflexus evolved multiple resistance to two classes of PSII (HRAC group C1 and C2), 10 to ALS and PSII inhibitors, 11 whereas another biotype proved to be resistant to ALS and PPO inhibitors. 12 Dioecious species evolved a number of complex two-and three-way multiple resistance 6 with A. tuberculatus that became multiple resistant to up to six SoA (ALS, PSII, EPSPS, PPO, HPPD inhibitors and synthetic auxins).…”
Section: Introductionmentioning
confidence: 99%